Karakterisasi sumber gempa Yogyakarta 2006 berdasarkan data GPS - Sulaeman, Cecep; Dewi, Lestari Cendekia; Triyoso, Wahyu (Indonesian Journal on Geoscience, 2008)
http://dx.doi.org/10.17014/ijog.vol3no1.20085The southern part of Central Jawa is one of earthquake hazard prone areas in Indonesia an earthquake occurred on May 27, 2006 and had the moment magnitude 6.3. Base on the GPS observation, the characterization of the epicenter and source of this Yogyakarta earthquake can be estimated using the displacement estimation and strain at the measurement point by using a simple kriging and sequential gaussian simulation method. The direction of the displacement and maximum shear strain anomaly in this research was shown by the fault of SW â NE direction and the displacement pattern shows that this fault is left lateral strike slip movement. The positive anomaly of the maximum shear strainis located about 10 km east of Bantul, which suggests as the position of Yogyakarta 2006 earthquake source, with the moment seismic and moment magnitude values are 8.1385 x 1025 dyne cm, and 6.5 respectively. Â  Â